2022
DOI: 10.1186/s40359-022-00911-8
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and stress among Iranian nurses in COVID-19 care wards

Abstract: Background Nurses are at the frontline of care provision to patients with coronavirus disease 2019 (COVID-19). The high communicability of COVID-19, high levels of stress associated with the disease, and challenges of care provision to afflicted patients faced nurses in Iran with problems such as depression, anxiety, and stress. The aim of the study was to assess depression, anxiety, and stress among Iranian nurses who provided care to patients with COVID-19. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
(70 reference statements)
0
9
1
Order By: Relevance
“…Also, the prevalence rates of extremely severe stress and anxiety were 15.2% and 89.1%, respectively. A study showed that the prevalence rates of moderate to severe stress and anxiety in Iranian nurses in COVID‑19 care wards were 23.7% and 61.3%, respectively [ 5 ]. Also, Sheikhbardsiri et al reported that the mean scores of stress and anxiety in nurses at educational hospitals during the COVID-19 pandemic were at a moderate level [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the prevalence rates of extremely severe stress and anxiety were 15.2% and 89.1%, respectively. A study showed that the prevalence rates of moderate to severe stress and anxiety in Iranian nurses in COVID‑19 care wards were 23.7% and 61.3%, respectively [ 5 ]. Also, Sheikhbardsiri et al reported that the mean scores of stress and anxiety in nurses at educational hospitals during the COVID-19 pandemic were at a moderate level [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean score of stress and anxiety of all nurses were 14.13 ± 2.56 and 13.06 ± 2.86, respectively. Several previous studies reported that the mean score of stress was 9.62 ± 4.94 [ 4 ], 15.13 ± 4.76 [ 5 ], and 16.23 ± 9.25 [ 6 ] among nurses in Iran during the COVID-19 pandemic. Also, they reported that the mean score of anxiety was 10.32 ± 4.85 [ 4 ], 13.21 ± 4.90 [ 5 ], and 12.65 ± 9.52 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the entire world has experienced infectious diseases in the past, the COVID‐19 pandemic as a new infectious disease has greatly disrupted the public health systems of countries (Irandoost et al, 2022). As the largest group of healthcare providers, nurses are on the front lines of providing care to patients with COVID‐19 and spend a lot of time in close contact with them (Sharifi et al, 2022). Despite the crucial role of nurses in controlling and preventing the virus and its complications (Zamanzadeh et al, 2021), the COVID‐19 pandemic created undesirable effects on their working conditions (Fernandez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%